2023
DOI: 10.1021/acssensors.2c02291
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Computational Study of a Chemiresistive NO2 Gas Sensor Based on the Carbon Dots-WO3 Heterostructure for Operating below Room Temperature

Abstract: For a long time, chemiresistive gas sensors based on metal oxide semiconductors (MOSs) suffer from higher operating temperatures, resulting in higher energy consumption and instability of the sensors. Generally, a MOS-based chemiresistive gas sensor being able to work at room temperature is considered to be outstanding already. Here, a highly sensitive NO2 gas sensor based on the carbon dots-WO3 heterostructure, which can work below room temperature at –6 °C, is fabricated. At 18, –1, and –6 °C, its detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…As a common gas in industrial production, nitrogen dioxide (NO 2 ) can lead to grave respiratory problems, including inflammation of the trachea and accumulation of fluid in the lungs. Moreover, recent investigations have shown that NO 2 is closely related to the prevention and transmission of COVID-19. , And it is also a significant account of environmental pollution such as summer smog, acid rain, and PM 2.5, which poses a major endangerment to mankind’s health and the safety of other life on the earth. , According to the OSHA regulations, the maximum concentration of short-term exposure to NO 2 is 5 ppm in industry. Long-term exposure to high concentrations of NO 2 can lead to poor breathing, lung disease, and even death. , Additionally, nitric oxide (NO) is a major contributor to air pollution and can have an unfavorable influence on mankind’s health. It can cause respiratory problems and cardiovascular diseases and result in the formation of smog and particulate matter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a common gas in industrial production, nitrogen dioxide (NO 2 ) can lead to grave respiratory problems, including inflammation of the trachea and accumulation of fluid in the lungs. Moreover, recent investigations have shown that NO 2 is closely related to the prevention and transmission of COVID-19. , And it is also a significant account of environmental pollution such as summer smog, acid rain, and PM 2.5, which poses a major endangerment to mankind’s health and the safety of other life on the earth. , According to the OSHA regulations, the maximum concentration of short-term exposure to NO 2 is 5 ppm in industry. Long-term exposure to high concentrations of NO 2 can lead to poor breathing, lung disease, and even death. , Additionally, nitric oxide (NO) is a major contributor to air pollution and can have an unfavorable influence on mankind’s health. It can cause respiratory problems and cardiovascular diseases and result in the formation of smog and particulate matter.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term exposure to high concentrations of NO 2 can lead to poor breathing, lung disease, and even death. 8,9 Additionally, nitric oxide (NO) is a major contributor to air pollution and can have an unfavorable influence on mankind's health. It can cause respiratory problems and cardiovascular diseases and result in the formation of smog and particulate matter.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A chemiresistive NO 2 sensor is a device that detects and quantifies the concentration of nitrogen dioxide gas in the air using a chemiresistive transducer. , The principle of operation involves the change in the electrical resistance of a sensing material upon exposure to NO 2 gas. Conducting polymers (CPs), such as polyaniline, polythiophene, and polypyrrole, are commonly used as sensing materials due to their high sensitivity and selectivity toward NO 2 gas. The chemiresistive NO 2 sensor has several advantages over other types of sensors, including low power consumption, simple configuration, and high sensitivity. , …”
Section: Introductionmentioning
confidence: 99%
“…The ability of the platform to show matching redox activity is the key to improve the sensitivity and selectivity . To achieve this, semiconductors and noble metals having catalytic facets for adsorption/desorption and reactivity , were engineered together for ppb/μM level of detection. , …”
mentioning
confidence: 99%
“…15 To achieve this, semiconductors and noble metals having catalytic facets for adsorption/desorption and reactivity 16,17 were engineered together for ppb/μM level of detection. 18,19 According to the Food and Agriculture Organization (FAO), tomato is the second most important vegetable crop after potato. Its wide cultivation makes it susceptible to insect herbivory, especially Tuta absoluta, which is an economically important pest.…”
mentioning
confidence: 99%